Impact of ecological factors on development of Botryodiplodia rot of guava fruit - Pawar, Vasant P (Current Botany, 2012)
Effect of temperature and relative humidity on severity of Botryodiplodia rot of guava fruit was studied. Low temperature and low relative humidity inhibited severity of disease.